Xiaozhang Tie Improves Intestinal Motility in Rats With Cirrhotic Ascites by Regulating the Stem Cell Factor/c-kit Pathway in Interstitial Cells of Cajal - Zhao, Qiang; Xing, Feng; Tao, Yanyan; Liu, Hongliang; Huang, Kai; Peng, Yuan; Feng, Nianping; Liu, Chenghai (Frontiers in Pharmacology, 2020)
We previously discovered that Xiaozhang Tie (XZT) was helpful for cirrhotic ascites, with obvious abdominal distention relief, suggesting that it may improve gastrointestinal (GI) motility. However, the underlying mechanisms of GI motility in cirrhotic ascites are unclear. Here, we aimed to discover explored the effect of XZT on GI motility in animal cirrhotic ascites and probed the action mechanism affecting GI motility by regulating the stem cell factor (SCF)/c-kit pathway in interstitial cells of Cajal (ICCs) and GI hormones. First, rat models of cirrhotic ascites were developed and then divided randomly into the following three subgroups: model control, XZT group, and mosapride group. The efficacy of XZT on treating cirrhotic ascites was evaluated on the basis of ascites weight and volume, 24 h urine volume, and feces water content. GI motility of the cirrhotic model, intestine propulsion, and gastric residue were detected using the migration distance of ink in vivo, and the frequency of contraction and tension of isolated gastric and jejunal muscle strips were measured after incubation with XZT extracts. Serum GI hormone content, including motilin (MTL), substance P (SP), somatostatin (SS), and vasoactive intestinal polypeptide were assayed. Subsequently, ICCs were isolated from jejunum, and primarily cultured ICCs were incubated with and without XZT and SCF. The cell vitality of the ICCs was measured. A whole-cell patch recording technique was used to record the current of K+ and Na+ channels in the ICC membrane. Expressions of c-kit/p-c-kit, p-Akt, p-STAT3, and p-Erk1/2 were detected in vivo and in vitro. The results revealed that XZT significantly reduced ascites weight and increased urine volume and fecal water content in model rats. XZT promoted intestinal motility and increased MTL level but reduced SP and SS levels. It enhanced the current of Na+ and K+ in ICCs and improved c-kit expression and signaling mediator phosphorylation in SCF/c-kit, which was inhibited by imatinib in vitro and downregulated in model rats in vivo. Our study concluded that XZT reduced the amount of ascites and improved intestinal motility in cirrhotic rats, which may be associated with its effect on ascites and was involved in the mechanisms regulating the SCF/c-kit signaling pathway in ICCs and improving gastrointestinal hormone secretion.